Population biology of dominant fish species in Matang Mangrove Estuaries, Perak, Malaysia - Mohd Khatib, Mohd Azim (2020)
Matang Mangrove Estuaries, which are situated in the western shore of Peninsular Malaysia, are the main and important part of mangrove forest in Malaysia. In order to assess the stock status of the fishes in Matang Mangrove Estuaries, it is necessary to understand the key population parameters. The objective of this study is to determine several aspects of population biology of fishes over there such as species composition, spatio-temporal distribution, diversity indices, population dynamic parameters and feeding habits. The study was conducted between September 2015 and August 2016. There were three sampling stations and fish samples were collected by using push net from each station. In total, 39 fishes, 1 crab and 3 shrimp’s species were identified from the study areas. Among them, five fish species (Escualosa thoracata, Thryssa hamiltonii, Ambassis nalua, Stolephorus tri and Johnius belangerii) were the most dominant (> 2%). The abundance of 10 species was found to be correlated (positive or negative) with the water quality parameters. The highest and significant regression coefficient was observed for Nemipterus nemurus which indicated that 37% of their abundance was influenced by the major water quality parameters and the remaining 63% by other unknown factors. The species richness index showed a significant variation within the monsoon and intermonsoon seasons, peaking in the months of December - February and April – June. Shannon-wiener Index also clearly indicated two peaks in a year; with one peak in Febuary and another in June. The growth, mortality, exploitation and recruitment of the five dominant fishes (E. thoracata, T. hamiltonii, A. nalua, S. tri and J. belangerii) were estimated based on length-frequency data, using FiSAT software. In terms of length-weight relationships, A. nalua, S. tri and J. belangerii showed a negative allometric growth while E. thoracata and T. hamiltonii showed an isometric growth in the Matang Mangrove Estuaries. Recruitment pattern was continuous with two major peaks for T. hamiltonii, A. nalua, S. tri and J. belangerii while it was one major peak for E. thoracata. The exploitation level (E) of E. thoracata, T. hamiltonii, A. nalua, S. tri and J. belangerii were 0.41, 0.48, 0.51, 0.54 and 0.52, respectively. This indicates that the stock of E. thoracata and T. hamiltonii were 18% and 4% under-exploited, respectively. Meanwhile, the fisheries of A. nalua, S. tri and J. belangerii are found to be above the optimum level of exploitation (E > 0.50). According to the simple resultant index (% Rs), plant (phytoplankton, algae and plant leave) and animal (zooplankton, unidentified fish parts, fish and crustacean parts) based diets contained 42.09% and 44.40% for E. thoracata, 50.11% and 38.24% for T. hamiltonii, 50.35% and 37.99% for A. nalua, 38.17% and 46.55% for S. tri, 25.35% and 58.86% for J. belangerii. Therefore, all observed five fish species could be considered as omnivorous based on stomach contents. The similarity between diets varied from 60-80% during the wet and dry season. During the dry season, stable carbon and nitrogen isotope values of the samples had less variation, indicating narrow dietary sources compared to the wet season where the distribution of their isotopic values was larger.